2017
DOI: 10.1007/s11682-017-9777-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of overnight fasting on intrinsic functional connectivity: a double-blind fMRI study

Abstract: The human brain depends mainly on glucose supply from circulating blood as an energy substrate for its metabolism. Most of the energy produced by glucose catabolism in the brain is used to support intrinsic communication purposes in the absence of goal-directed activity. This intrinsic brain function can be detected with fMRI as synchronized fluctuations of the BOLD signal forming functional networks. Here, we report results from a double-blind, placebo controlled, cross-over study addressing changes in intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
0
10
0
1
Order By: Relevance
“…The duration of fasting in human studies typically ranges from 2 to 24 h 24 , 29 , 30 . Overnight fasting for 12–14 h has been commonly used to detect relationships between fasting and cognition in humans 31 , 32 . Imaging findings showed that 14 or 16 h of overnight fasting significantly increased the activation of brain areas that are related to cognition 23 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of fasting in human studies typically ranges from 2 to 24 h 24 , 29 , 30 . Overnight fasting for 12–14 h has been commonly used to detect relationships between fasting and cognition in humans 31 , 32 . Imaging findings showed that 14 or 16 h of overnight fasting significantly increased the activation of brain areas that are related to cognition 23 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, an effort was made to establish a similar gastric state at each experimental session, using a fixed schedule and fixed breakfast. Researchers have probed the effect of gastric state, including overnight fasting, on rsfMRI outcomes [55,56]. Concurrent EGG would allow future studies in this area to benefit from measures of how gastric state affects stomach-brain synchronization.…”
Section: What Is Your Stomach Saying To Your Brain?mentioning
confidence: 99%
“…Second, the selection of brain networks was motivated by their role in cognition specifically to highlevel cognitive constructs such as attention and cognitive control and their relevance in the literature . While we perceive this selection as well-motivated and we have demonstrated their sensitivity (14), it is a subjective pre-selection. We might not cover other cognitive processes and associated brain networks equally well.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, these time-course matrices are employed in a linear model fit against the subject's fMRI data set to estimate subject-specific spatial maps. From these subject-wise expressions of the 10 networks, we selected four networks of interest (the left and right lateralized fronto-parietal attention networks, FPN; the executive control network, ECN; and the default mode network, DMN), due to their importance in the neuroimaging field, their comparatively clear functional profile and their importance in mental disease or previous microbiome research (10,11,(14)(15)(16). The different spatial maps for all participants are combined into a single 4D file per target network.…”
Section: Generation Of Subject-specific Functional Connectivity Mapsmentioning
confidence: 99%
See 1 more Smart Citation